Effect of neuromuscular electrical stimulation therapy using the StimaWELL 120MTRS system on erector spinae morphology in patients with chronic low back pain - Balthazard, Loïck; Wolfe, Daniel; Fortin, Maryse (Frontiers in Musculoskeletal Disorders, 2023)
Objective: Chronic low-back pain (CLBP) is the leading cause of disability globally. CLBP is associated with a decrease in cross-sectional area (CSA) and an increase in fat infiltration (FI) of the lumbar paraspinal muscles, such as erector spinae (ES). Neuromuscular electrical stimulation (NMES) therapy showed promising outcomes in the treatment of CLBP, but its impact on ES morphology is unknown. Therefore, this study aimed to compare the effect of two NMES protocols on ES CSA and FI in a cohort of patients with CLBP. Methods: Twenty participants with CLBP (aged 18-60 years old) were randomized into the phasic (n=11) or the combined (n=9) protocol groups. They completed a 10-week (20 sessions) NMES therapy using the StimaWELL 120MTRS device. Magnetic resonance imaging (MRI) examinations were acquired at baseline and post-intervention to assess ES CSA and FI at all spinal levels (e.g., L1-L2 to L5-S1). Statistical analyses were conducted to assess the effect of the intervention on ES morphology irrespective of groups, and between groups. Results: Irrespective of groups, participants showed a decrease in left ES CSA (p=0.005) at L2-L3 and left ES FI at L5-S1 (p=0.040). We also observed a greater decrease in ES FI in the combined protocol compared to the phasic protocol on the right side at L3-L4 (p=0.029) and L4-L5 (p=0.015). No other changes in ES CSA or FI were observed (p>0.05). Conclusion: NMES therapy demonstrated minimal effect on ES morphology in patients with CLBP. Further research is needed to extend and confirm our findings.